Changes in nutritional status, risk factors and food intake in stroke subjects: cohort study analysis of non-communicable disease risk factors - Gigir, Engelien Milannia; Sukandar, Dadang; Marliyati, Sri Anna (Indonesian Nutrition Association, 2024)
Background: Stroke is a major cause of death and disability worldwide, affecting 15 million people annually. In Indonesia, the prevalence is 10.9%. Major risk factors include high blood pressure, obesity, inactivity, poor diet, and smoking. Objective: This study aims to analyze long-term trends in risk factors, nutritional status, and food intake among stroke patients from 2011-2021, assessing their impact on stroke incidence. Methods: Data from a longitudinal cohort study of 5,329 subjects, including 215 stroke patients, were analyzed using Microsoft Excel 2019 and SAS software. ANOVA was used to assess annual changes in risk factors, nutritional status, and food intake. Survival analysis was conducted with SAS PROC LIFETEST and PROC LIFEREG. Results: The cohort was primarily female (62.8%), aged 60 or older (57.2%), senior high school education (25.6%), civil servants (30.7%), and low income (57.2%). Significant changes were noted in BMI (p=0.037), fasting blood glucose (FBG) (p=0.001), HDL (p=0.049), abdominal circumference, smoking habits, physical activity (p<0.001), protein intake (p=0.026), and intake of energy, fat, carbohydrates, and sodium (p<0.001). Factors significantly associated with stroke included age, FBG, postprandial glucose, smoking (p<0.0001), LDL (p=0.0380), HDL (p=0.0126), physical activity (p=0.0455), energy intake (p=0.0002), fat intake (p=0.0007), and sodium intake (p=0.0012). Conclusions: The study highlights significant changes in nutritional status, glucose levels, HDL cholesterol, physical activity, and smoking habits. These factors, along with age, cholesterol levels, and dietary intake, impact stroke incidence, underscoring the need for comprehensive stroke prevention strategies.